Revitalization of Waqf: Historical Legacy and Potential in Addressing Muslim Socio Economic Disparities in India - Muhammed Fatheen Mk (Penerbit Hellow Pustaka, 2026)
Waqf constitutes the economic foundation of Islamic civilization, as noted by historian Marshall Hodgson. This paper examines waqf’s untapped potential in India’s contemporary economy, where 38% of Muslims live in poverty despite the presence of waqf properties valued at 1.2 trillion Indian Rupees according to the Sachar Committee Report. The inefficiencies in waqf administration originated during colonial rule when imperial powers, viewing these endowments financially lucrative, appointed supervisors based primarily on language proficiency rather than expertise. Post-colonial governments perpetuated this interventionist approach through legislative amendments that enhanced state control, despite recommendations from various inquiry committees. Administrative inconsistencies have undermined waqf’s effectiveness, exemplified by the Central Waqf Council’s chairperson simultaneously serving as the portfolio minister-creating a problematic governance structure where 1% of annual returns fund this self-referential advisory mechanism. Such administrative disorders significantly contribute to the continued socioeconomic vulnerability of India’s Muslim community. Historical analysis reveals waqf’s profound impact on social welfare systems across civilizations, influencing European philanthropic models as evidenced by the Franciscan Friars theory and the University of Oxford’s endowment principles through the concept of Usés. Contemporary, waqf models demonstrate potential returns averaging 31% annually. Cash awqaf, incorporated through the Musalman Waqf Validity Act IV of 1913, represents a particularly promising avenue. This research addresses jurisprudential divergences by examining Ottoman Isthighlal practices and proposes implementing Imam Zufar’s waqf chain model in collaboration with the Islamic Development Bank and Islamic Research and Training Institute, adapted to the Indian context. Drawing from successful examples like Turkey’s Vehbi Koç Foundation and Malaysia’s Finterna Waqf blockchain initiative, this paper advocates for democratization and decentralization of waqf administration in India and extending the Public Premises Act of 1958 to waqf properties to streamline recovery of encroached assets. The proposed venture philanthropy framework aims to enhance socio- religious confidence among Indian Muslims while addressing critical economic vulnerabilities through institutional reform that acknowledges both historical legacies and contemporary realities.